Politeness Strategies Used by An English Teacher in Making Request at The Eleventh-Grade Students of SMAN Cimanggung Sumedang - R. Santosa, Tinanthy; H. Pratama, Shadam Hussaeni; S. Widianingsih, Ayang W. (Ma'soem University, 2024)
In teaching English, the teacher has a role in creating a classroom atmosphere that makes students willing to learn. There are politeness strategies that can be used by teachers in requesting students. This study aims to find the types of politeness strategies used and to find the implications of using politeness strategies in the teaching and learning process. To analyse the politeness strategies used by the teacher, a theory proposed by Brown and Levinson (1978) is used. The politeness strategies are bald on record, positive politeness, negative politeness, and off record. This study uses qualitative research with descriptive analysis at the eleventh-grade class in SMAN Cimanggung. As the result, there are four politeness strategies used by teacher in making request: bald on record, positive politeness, negative politeness, and off record. This study also found out the implications of using politeness strategies are effective communication, cooperative interaction, and less imposition. Besides, the result can be used as evaluation material for teachers and schools in using politeness strategies to persuade the students to fulfill the request. For further studies can be conducted at a different focus thus the use of politeness strategies will more revealed.